2024
DOI: 10.3389/fpsyt.2024.1265722
|View full text |Cite
|
Sign up to set email alerts
|

Understanding suicidal ideation disparity between sexual minority and heterosexual Chinese young men: a multiple mediation model of social support sources, self-esteem, and depressive symptoms

Yiting Huang,
Jiayu Liu,
Gang Huang
et al.

Abstract: ObjectivesAlthough sexual minorities have reported higher levels of suicidal ideation than heterosexuals across cultures, the role of various psychosocial factors underlying this disparity among young men has been understudied, particularly in China. This study examined the multiple mediating effects of psychosocial factors between sexual orientation and suicidal ideation in Chinese sexual minority and heterosexual young men.Methods302 Chinese cisgender men who identified as gay or bisexual, and 250 cisgender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Their findings revealed that non-heterosexual college students exhibited a higher risk of PLEs with stratified analysis revealing a significant association for female students. In another study exploring mental health issues among sexual minorities, Huang et al (5) found that young men from sexual minority groups had higher levels of reported suicidal ideation and lower social support than their heterosexual counterparts. They identified enhancing social support and selfesteem as possible psychosocial interventions to reduce suicidality in men belonging to sexual minorities.…”
mentioning
confidence: 99%
“…Their findings revealed that non-heterosexual college students exhibited a higher risk of PLEs with stratified analysis revealing a significant association for female students. In another study exploring mental health issues among sexual minorities, Huang et al (5) found that young men from sexual minority groups had higher levels of reported suicidal ideation and lower social support than their heterosexual counterparts. They identified enhancing social support and selfesteem as possible psychosocial interventions to reduce suicidality in men belonging to sexual minorities.…”
mentioning
confidence: 99%